ADRESSING NON-COMPLIANCE WITH HALAL PRODUCT REGULATIONS IN INDONESIA: SAFEGUARDING MUSLIM CONSUMER RIGHTS - Purwaningsih, Prihatini; Mustika, Desty Anggie; Purwoto, Ady (Kanun Jurnal Ilmu Hukum, 2024)
This article examines the persistent non-compliance of producers with halal product regulations in Indonesia and its implications for safeguarding the rights of Muslim consumers. Despite the enactment of the Halal Product Assurance Law in 2014, a significant discrepancy exists between regulatory mandates and actual adherence. Through a normative-juridical approach involving legal interpretation and analysis of government reports and academic literature, this study delves into the various factors contributing to this issue. The research findings indicate that non-compliance arises from a combination of regulatory uncertainties, institutional inefficiencies, and socio-economic challenges. Notably, inadequate enforcement mechanisms, overlapping institutional jurisdictions, and the financial burden of certification processes are identified as key factors. This non-compliance undermines the halal integrity of products, thereby violating the rights of Muslim consumers as stipulated by Islamic law. Resolving this issue necessitates a comprehensive overhaul of the halal certification system, encompassing streamlined procedures, improved inter-agency collaboration, and strengthened enforcement measures. These efforts contribute to the broader dialogue on religious consumer rights and regulatory adherence in diverse societies, offering valuable insights for policymakers and stakeholders in the halal sector.